Effects of CME and CIR induced geomagnetic storms on low-latitude ionization over Indian longitudes in terms of neutral dynamics. Issue 1 (1st January 2020) - Chakraborty, S.; Ray, S.; Sur, D.; Datta, A.; Paul, A.
Highlights: October 2016 presents a unique case of CME and CIR induced events. Drastic enhancement inTEC as a result of the CIR-induced event of October 2016. Positive enhancement of TEC observed for both the storms due to neutral wind. Different observing stations ensure characterization of storm-induced effects on TEC. At low solar activity, storm induced electrodynamics produce 20–45 TECU enhancement. Abstract: This paper presents the response of the ionosphere during the intense geomagnetic storms of October 12–20, 2016 and May 26–31, 2017 which occurred during the declining phase of the solar cycle 24. Total Electron Content (TEC) from GPS measured at Indore, Calcutta and Siliguri having geomagnetic dips varying from 32.23°N, 32°N and 39.49°N respectively and at the International GNSS Service (IGS) stations at Lucknow (beyond anomaly crest), Hyderabad (between geomagnetic equator and northern crest of EIA) and Bangalore (near magnetic equator) in the Indian longitude zone have been used for the storms. Prominent peaks in diurnal maximum in excess of 20–45 TECU over the quiet time values were observed during the October 2016 storm at Lucknow, Indore, Hyderabad, Bangalore and 10–20 TECU for the May 2017 storm at Siliguri, Indore, Calcutta and Hyderabad. The GUVI images onboard TIMED spacecraft that measures the thermospheric O/N2 ratio, showed high values (O/N2 ratio of about 0.7) on October 16 when positive storm effects were observed compared to the other days during the storm period. The observed features have been explained in terms of the O/N2 ratio increase in the equatorial thermosphere, CIR-induced High Speed Solar Wind (HSSW) event for the October 2016 storm. The TEC enhancement has also been explained in terms of the Auroral Electrojet (AE), neutral wind values obtained from the Horizontal Wind Model (HWM14) and equatorial electrojet strength from magnetometer data for both October 2016 and May 2017 storms. These results are one of the first to be reported from the Indian longitude sector on influence of CME- and CIR-driven geomagnetic storms on TEC during the declining phase of solar cycle 24.